The Relevance of Criminology and Penology in the Criminal Justice System - Hasrul Buamona; Wulan Julianti Putri; Axcell Ezhalio Melvin Kaya; Dhea Meisa (Universitas Muhammadiyah Tangerang, 2024)
The case of Nenek Minah was a criminal matter that shocked the Indonesian public in 2009. Nenek Minah was sentenced by the Purwokerto District Court to a conditional prison term of 1 month and 15 days, with a 3-month probation period, based on Article 362 of the Criminal Code (KUHP). This research was conducted using a normative juridical method, questioning two primary issues regarding the relevance of criminology and penology within the criminal justice system. First, what is the relevance between criminology and penology in the criminal justice system? Second, what is the pattern of relevance between criminology and penology based on empirical cases within the criminal justice system. The results of the study show that criminology serves as a provider of scientific databases regarding the root causes of crime and perpetrator profiles, while penology formulates handling strategies that are applicative, educative, and rehabilitative. The synergy between these two disciplines is crucial for achieving the goals of public protection and the improvement of inmate behavior. Furthermore, the retributive paradigm must be shifted toward a progressive paradigm that is more humanist and rehabilitative within the framework of the new criminal justice system.